2007
DOI: 10.1111/j.1872-034x.2007.00109.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of HBV infection in Japan

Abstract: Hepatitis B virus (HBV) is usually transmitted from mother to infant, and genotype C is prevalent in Japan. Because of these features, guidelines for HBV treatment from other countries are not directly adaptable to Japanese patients. Age is an important factor in deciding the treatment strategy, because many vertically transmitted HBV carriers naturally show spontaneous remission by the age of 25-30 years. In addition, genotype C is considered more refractory to antiviral therapies than genotypes A and B. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
0
9
1
Order By: Relevance
“…A Japanese multicenter collaborative trial of sequential therapy following a similar method to Saferty et al . also found no significant enhancement of therapeutic efficacy in comparison to IFN monotherapy as a historical control . However, this study did show that in almost all responders, HBeAg negative conversion occurred during initial lamivudine monotherapy.…”
Section: Pharmacotherapy (2) – Nascontrasting
confidence: 59%
“…A Japanese multicenter collaborative trial of sequential therapy following a similar method to Saferty et al . also found no significant enhancement of therapeutic efficacy in comparison to IFN monotherapy as a historical control . However, this study did show that in almost all responders, HBeAg negative conversion occurred during initial lamivudine monotherapy.…”
Section: Pharmacotherapy (2) – Nascontrasting
confidence: 59%
“…Sequential lamivudine and interferon therapy induced less viral resistance to lamivudine than lamivudine monotherapy and appeared to have a better biochemical response than interferon or lamivudine monotherapy. The sequential administration of lamivudine and interferon can reduce treatment duration of each drug, resulting in less chance of viral resistance for lamivudine and less side effects from interferon [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, sequential entecavir and IFN therapy does not show evidence of superior therapeutic effects. Some studies of lamivudine and IFN sequential therapy indicated that the biochemical and virological responses were comparable or superior to lamivudine or interferon monotherapies [29,30], but no consistent assessment of the therapy exists. For young HBeAg-negative patients with HBV DNA of less than 7 log copies/ml, observation over time as a basic principle is generally considered acceptable, but in patients with intermittent ALT levels of at least 31 IU/ml, long-term IFN administration is recommended.…”
Section: Treatment Guidelines For Chronic Hepatitis Bmentioning
confidence: 98%